The Impact of Stress Management Training on Reducing Stress Levels in Adolescents at the Mamuju Detention Center - Zulhaini Sartika A. Pulungan; Edi Purnomo; Achir Yani S. Hamid (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Teenagers in detention centres often experience high levels of stress due to loss of freedom, an uncertain future, and social stigma. This study aims to determine the effect of stress management training on the stress level of adolescent inmates in detention centres. Methods: Quasi-experimental research with pre-post test with control group design. The study sample was 72, divided into intervention and control groups of 36. Purposive sampling technique. Stress management training was conducted in 8 sessions. Instrument used: Depression Anxiety Stress Scale 42. Data analysis with paired t-test and independent t-test. Results: The average age of respondents in the control group was 20.42 years, and the intervention group was 19.94 years. All respondents were male. The last education of the majority of respondents was high school; the control group was 55.6%, while the intervention was 69.4%. Most jobs before entering the prison were self-employed; the control group was 47.2%, while the intervention was 55.6%. Most cases were narcotics; the control group was 44.4%, while the intervention was 41.7%. The average length of stay in the detention centre in the control group was 2.69 months, while the intervention group was 2.61 months. There was a significant difference in reduced stress levels between the intervention and control groups (p = 0.002; d = 0,75). Conclusion: Stress management training lowers stress levels in adolescents in Rutan. These findings open up an excellent opportunity to develop more holistic rehabilitation programs that focus on the recovery and self-development of juvenile inmates. To maximize the positive impact of the study's findings, the researchers recommend that correctional institutions integrate stress management training programs into existing rehabilitation programs.